Au–Pd bimetallic nanoparticles supported on a high nitrogen-rich ordered mesoporous carbon as an efficient catalyst for room temperature Ullmann coupling of aryl chlorides in aqueous media. Issue 52 (8th June 2018) - Karimi, Babak; Barzegar, Hossein; Vali, Hojatollah
Abstract : An ionic liquid derived highly nitrogen-rich mesoporous carbon supported Au–Pd alloy was found to be an efficient and recyclable catalyst for the Ullmann coupling reaction of various aryl chlorides at room temperature. Abstract : An ionic liquid derived highly nitrogen-rich mesoporous carbon supported Au–Pd alloy was found to be an efficient and recyclable catalyst for the Ullmann coupling reaction of various aryl chlorides at room temperature in aqueous media.